(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The finding of Strepsiptera first instar larvae in pollen loads of Apis mellifera L. is reported. The biology of some Strepsiptera involves, indeed, that the larvae are laid upon flowers and so they may be pieked up by workers of honeybees collecting nectar and pollen. The samples of pollen loads were taken from hives situated in two sites of the central Italian Alps by means of special traps, which were inspected weekly from mid-April to mid-October over two years (1992 and 1993). The pellets were subjected to filth-test using an analytical method especially devised for the purpose, which permitted the extraction of Arthropods (insects and mites) and their fragments included in the pollen loads. Most of the specimens found were Strepsiptera first instar larvae, and they varied in number according to the season. In no case were observed stylopized bees: this would suggest that the presence of Strepsiptera larvae in the pollen loads is merely a causal consequence of the bees’ antophylous behaviour.